2022
DOI: 10.1007/s00246-022-03006-8
|View full text |Cite
|
Sign up to set email alerts
|

What is Known About Critical Congenital Heart Disease Diagnosis and Management Experiences from the Perspectives of Family and Healthcare Providers? A Systematic Integrative Literature Review

Abstract: The experience of diagnosis, decision-making and management in critical congenital heart disease is layered with complexity for both families and clinicians. We synthesise the current evidence regarding the family and healthcare provider experience of critical congenital heart disease diagnosis and management. A systematic integrative literature review was conducted by keyword search of online databases, MEDLINE (Ovid), PsycINFO, Cochrane, cumulative index to nursing and allied health literature (CINAHL Plus) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Over 50% of maternal and child health practitioners endorsed termination in instances of congenital heart disease and phenylketonuria. The diagnostic journey, decision-making process, and subsequent management of critical congenital heart disease introduce a multifaceted challenge for clinicians and families ( 26 ). Particularly, the diagnosis and treatment of a critically ill congenital heart disease child significantly impact parents’ health and wellbeing, and the experience is profoundly stressful and transformative for families ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 50% of maternal and child health practitioners endorsed termination in instances of congenital heart disease and phenylketonuria. The diagnostic journey, decision-making process, and subsequent management of critical congenital heart disease introduce a multifaceted challenge for clinicians and families ( 26 ). Particularly, the diagnosis and treatment of a critically ill congenital heart disease child significantly impact parents’ health and wellbeing, and the experience is profoundly stressful and transformative for families ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic journey, decision-making process, and subsequent management of critical congenital heart disease introduce a multifaceted challenge for clinicians and families ( 26 ). Particularly, the diagnosis and treatment of a critically ill congenital heart disease child significantly impact parents’ health and wellbeing, and the experience is profoundly stressful and transformative for families ( 26 ). Regarding phenylketonuria, despite the availability of clear treatment options, the prognosis varies, and continuous treatment from the neonatal period, with lifelong treatment recommended ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in the period after the child's heart surgery, 80% of the parents reported clinically significant trauma symptoms, with up to 30% meeting the criteria for a PTSD diagnosis [25]. The series of stressful events associated with the child's CHD might trigger subsequent other psychosocial stressors [26], like marital or financial issues [27], resulting in considerably high levels of distress experienced by parents [28].…”
Section: Introductionmentioning
confidence: 99%
“…In the period prior to the child's cardiac surgery, parental stress levels start to rise [29], followed by high levels of stress and anxiety during the whole peri-operative period [30]. Moreover, affected parents are reported to have an increased risk for mental health issues, particularly in the immediate post-surgery period [25,28]. Studies with longer follow-ups revealed mixed results on parental psychosocial adjustment after their child's heart surgery.…”
Section: Introductionmentioning
confidence: 99%